MEMODERINISASI KRIPIK UBI KAYU (OPAK) MENJADI PRODUK YANG SIAP BERSAING DI PASAR MODERN - Lismawati, Lismawati; Wijayanti, Indah Oktari (Nindikayla Institute, 2023)
The development of technology and information that is increasingly advanced at this time is still not fully understood by the community, especially among rural communities. This is shown by the lack of innovation made by residents in cassava food products, namely cassava chips (opak). Cassava chips (Opak) processed into various variants of processed cassava properly will have a positive impact on becoming a product of quality, quality, competitiveness and economic value. The community service program is to increase the knowledge and understanding of rural communities to have a high awareness of the concern for the utilization of abundant cassava from low value to competitive superior products. The method of implementation is by empowering the community with processed cassava raw material innovation activities and modernizing the form of cassava chips (opak) which is more marketable so that it can compete in the modern market. This activity involved the entire community of Sidodadi Village, Central Bengkulu. The results of this activity show that there is an increase in knowledge and interest in learning from the community to utilize the abundant cassava raw materials in the village into preparations that have high economic value and ultimately can help the economy and improve the quality of life of the villagers.